Financialisation of agricultural commodity and its trading during COVID-19 pandemic. (13th December 2021) - Mahalakshmi, S.; Thiyagarajan, S.; Naresh, G.
The establishment of regularised trading exchanges for agricultural commodities attracted every market participant to benefit from their trade. The pandemic has created massive chaos in every asset class, and agri-commodities are no exception. However, the pandemic also taught lessons for the global traders to focus on food produce. Therefore, this paper intends to look at agricultural commodity trading behaviour during this COVID-19 pandemic by looking at the movement of the trade in the agri-futures index and other asset classes, including equity, exchange rates, bullion prices, etc. The results show that all the selected asset classes except the exchange rate are influencing Agridex. In addition, the Agridex returns are influenced by the severity of COVID-19 cases. Therefore, the policymakers should keep this in mind and work to prevent the price rise to an uncontrollable extent because this can lead to stagflation.